Clinical observations from the clinical video head pulse test in patients with idiopathic horizontal semicircular canal light cupula - Song, Niu; Jingling, Chang; Wenyan, Xu; Xuemei, Pei (Frontiers in Neurology, 2024)
ObjectiveThe objective of the study is to analyze and explore the characteristics of the video head impulse test (vHIT) for light cupula in the idiopathic horizontal semicircular canal and compare them with those of horizontal semicircular canal cupulolithiasis (HC-cu) in order to investigate the potential mechanism involved.MethodsData from 51 cases of idiopathic light cupula and 42 cases of horizontal semicircular canal cupulolithiasis were retrospectively analyzed. The positional nystagmus features, vHIT anomaly rate, gain value, saccades, and other indicators were compared. SPSS 26 and Medcalc 22 were used to analyze the differences and correlations.ResultsThere were no differences in sex, age, the affected side, and positional nystagmus between the light cupula group and HC-cu group (p > 0.05). The overall abnormal rate of the vHIT (56.86% vs. 21.43%), the abnormal rate of the affected side (23.53% vs. 0.00%), and the saccade ratio of the affected side [40.0 (13.0, 76.0) vs. 6.0 (0.0, 15.0)] in the light cupula group were higher than those in the HC-cu group. The HC saccade ratio in the light cupula group was higher on the affected side than on the healthy side [40.0 (13.0, 76.0) vs. 11.0 (0.0, 38.0)], and the differences were statistically significant (p < 0.05). The receiver operating characteristic (ROC) curve analysis showed that the abnormal vHIT results and saccade ratio of the light cupula group were correlated with the affected side (p < 0.05).ConclusionThe vHIT results of idiopathic HC light cupula and HC-Cu were different as they are distinct diseases. Light cupula may be associated with some mild lesions in the vestibulo-ocular reflex (VOR) pathway. The lighter cupula theory is the possible mechanism.